A new perspective on board composition and firm performance in an emerging market - Ameer, Rashid; Ramli, Fairuz; Zakaria, Husein (Institut Pengurusan Penyelidikan, 2010)
This paper examines the relationship between board composition and firm performance in Malaysian listed non-financial firms using a board-level aggregation variable. The study utilized linear regression on a panel dataset of 277 firms observed over the period 2002–2007. The empirical results demonstrate that firm boards with a high representation of outside and foreign directors are associated with better performance compared to boards dominated by insider executive and affiliated non-executive directors. The findings suggest that in widely owned firms, a higher proportion of outsiders on the board helps reduce under-investment and agency problems, which carries significant economic implications. This research is noted as the first study to employ a board-level aggregation variable to demonstrate the impact of the board's resourcefulness on firm performance.